Energy Efficient Digital Omnichannel Marketing Based on a Multidimensional Approach to Network Interaction - Barykin, Sergey Evgenievich; Sergeev, Sergey Mikhailovich; Provotorov, Vyacheslav Vasilyevich; Lavskaya, Kristina Konstantinovna; Kharlamov, Andrey Viktorovich; Kharlamova, Tatiana Lvovna (Frontiers in Energy Research, 2022)
Digital Omnichannel marketing is viewed the answer to future marketing however, the concept is mired with problems related to the energy and carbon footprinting. Therefore, this study proposed energy efficient network of a complex topology of data access and marketting, where the nodes function as an objects with unique characteristics and create digital customer value network. It is believed that competition has transformed into a contest of online platforms in energy efficency as well in economic efficiency. It is emphasized that there is no alternative to multichannel interaction at the present stage of implementing digital business solutions. In this study, authors have developed omnichannel interaction algorithms based on mathematical models. The proposed approach supplements the digital twin model with economic indicators and methods. Results and analysis of multidimensional structures allows for omnichannel network digital interaction and improves the digital marketing approach. To consider the formation of a network configuration of customer service, developing the idea of digital interaction between participants in consumer value chains. The study conclude and recommend to expand the methodology of digital marketing involving alternative channels of interaction and energy efficency by including a mathematical apparatus for analyzing multidimensional structures (n-D structures).